Psychological skills of elite archery athletes - Bebetsos, E. (Journal of Human Sport & Exercise, 2015)
The purpose of this study was to examine age, sport/competition experience, and gender differences in psychological skills among Greek elite archery athletes. Seventy archery athletes completed a Greek version of the Athletic Coping Skills Inventory-28 by Smith, Schutz, Smoll, and Ptacek, during the 2011 Greek Men and Women National Archery Championship Tournament. Analyses yielded differences between age groups on two factors (freedom of worries and peaking with pressure). Additionally, differences were indicated between sport/competition experience groups on three factors (freedom of worries, confidence and concentration) but no statistically significant differences between sexes. Older athletes reported better emotional control, with less distress. Overall, results could help archery athletes become more familiar with the sport-specific psychological skills involved in their sport.